Signaling green: Investigating signals of expertise and prosocial orientation to enhance consumer trust. Issue 6 (9th September 2020) - Waites, Stacie F.; Stevens, Jennifer L.; Hancock, Tyler
Abstract: Prior research has established the positive effect of green marketing on purchase intentions. Less well known is why. Two empirical studies were conducted to investigate trust as an important mediator explaining the relationship between green marketing and purchase intentions. In study one, we successfully replicate prior research, again finding higher purchase intentions for companies that engage in green marketing. Additionally, trust in the company was found to mediate this relationship. Study two then examines the underlying mechanisms of expertise and prosocial orientation on the relationship between green marketing and trust, and then serially to purchase intentions. Demographic boundary conditions of age and gender were also investigated. Despite previous research indicating that gender affects perceptions of sustainable marketing, gender was not found to influence trust through perceptions of expertise and prosocial orientation. Interestingly, consumer age was found to influence perceptions of the company's expertise but not prosocial orientation. Younger consumers, specifically those about 38 and younger, believe that companies using green marketing display more expertise compared to those that do not, ultimately increasing perceptions of trust in the company.